Numerical Simulation of Airfoil Aerodynamic Penalties and Mechanisms in Heavy Rain. (7th November 2013) - Wu, Zhenlong; Cao, Yihua; Ismail, M.
Abstract : Numerical simulations that are conducted on a transport-type airfoil, NACA 64-210, at a Reynolds number of2.6 × 10 6 and LWC of 25 g/m 3 explore the aerodynamic penalties and mechanisms that affect airfoil performance in heavy rain conditions. Our simulation results agree well with the experimental data and show significant aerodynamic penalties for the airfoil in heavy rain. The maximum percentage decrease inC L is reached by 13.2% and the maximum percentage increase inC D by 47.6%. Performance degradation in heavy rain at low angles of attack is emulated by an originally creative boundary-layer-tripped technique near the leading edge. Numerical flow visualization technique is used to show premature boundary-layer separation at high angles of attack and the particulate trajectories at various angles of attack. A mathematic model is established to qualitatively study the water film effect on the airfoil geometric changes. All above efforts indicate that two primary mechanisms are accountable for the airfoil aerodynamic penalties. One is to cause premature boundary-layer transition at low AOA and separation at high AOA. The other occurs at times scales consistent with the water film layer, which is thought to alter the airfoil geometry and increase the mass effectively.